Integration and early testing of WEAVE: the next-generation spectroscopy facility for the William Herschel Telescope - Dalton, G; Trager, S; Abrams, DC; Lewis, I; Jin, S; Molaeinezhad, A; Schallig, E; Hughes, S; Brock, M; Terrett, D (Society of Photo-optical Instrumentation Engineers, 2020)
We present an update on the overall integration progress of the WEAVE next-generation spectroscopy facility for the William Herschel Telescope (WHT), now scheduled for first light in early-2021, with almost all components now arrived at the observatory. We also present a summary of the current planning behind the 5-year initial phase of survey operations, and some detailed end-to-end science simulations that have been implemented to evaluate the final on-sky performance after data processing. WEAVE will provide optical ground-based follow up of ground-based (LOFAR) and space-based (Gaia) surveys. WEAVE is a multi-object and multi-IFU facility utilizing a new 2-degree prime focus field of view at the WHT, with a buffered pick-and-place positioner system hosting 1000 multi-object (MOS) fibres, 20 mini integral field units, or a single large IFU for each observation. The fibres are fed to a single (dual-beam) spectrograph, with total of 16k spectral pixels, located within the WHT GHRIL enclosure on the telescope Nasmyth platform, supporting observations at R~5000 over the full 370-1000nm wavelength range in a single exposure, or a high resolution mode with limited coverage in each arm at R~20000.